2017
DOI: 10.1007/s00294-017-0698-3
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome profiling the cell cycle: lessons and challenges

Abstract: Understanding the causes and consequences of dynamic changes in the abundance and activity of cellular components during cell division is what most cell cycle studies are about. Here we focus on control of gene expression in the cell cycle at the level of translation. The advent of deep sequencing methodologies led to technologies that quantify the levels of all mRNAs that are bound by ribosomes and engaged in translation in the cell (Ingolia et al. Science 324:218-223, 2009). This approach has been applied re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 38 publications
(79 reference statements)
0
23
0
Order By: Relevance
“…We used centrifugal elutriation to obtain our synchronous cultures of 153 ribosomal protein paralog mutants. Unlike arrest-and-release synchronization approaches, 154 centrifugal elutriation maintains as much as possible the normal coupling of cell growth with cell 155 division (Aramayo and Polymenis, 2017;Soma et al, 2014). To collect enough cells for these 156 experiments, we followed the same approach as in our previous work on wild type cells (Blank 157 et al, 2017).…”
Section: Loss Of Rpl22ap Reduces Overall Protein Synthesis 133mentioning
confidence: 99%
“…We used centrifugal elutriation to obtain our synchronous cultures of 153 ribosomal protein paralog mutants. Unlike arrest-and-release synchronization approaches, 154 centrifugal elutriation maintains as much as possible the normal coupling of cell growth with cell 155 division (Aramayo and Polymenis, 2017;Soma et al, 2014). To collect enough cells for these 156 experiments, we followed the same approach as in our previous work on wild type cells (Blank 157 et al, 2017).…”
Section: Loss Of Rpl22ap Reduces Overall Protein Synthesis 133mentioning
confidence: 99%
“…To apply genome-wide methods for the identification of cell cycle-dependent changes in the abundance of molecules of interest, one must first obtain highly synchronous cell cultures. Preferably, synchronization must be achieved in a way that minimally perturbs cellular physiology and the coordination between cell growth and division (Mitchison, 1971; Aramayo and Polymenis, 2017). When cells are chemically or genetically arrested in the cell cycle to induce synchrony, known arrest-related artifacts can bias the results (Mitchison, 1971; Ly et al ., 2015; Aramayo and Polymenis, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Preferably, synchronization must be achieved in a way that minimally perturbs cellular physiology and the coordination between cell growth and division (Mitchison, 1971; Aramayo and Polymenis, 2017). When cells are chemically or genetically arrested in the cell cycle to induce synchrony, known arrest-related artifacts can bias the results (Mitchison, 1971; Ly et al ., 2015; Aramayo and Polymenis, 2017). An alternative synchronization method is elutriation, a physical process that fractionates an asynchronous cell population by cell size and sedimentation density properties of the cells, with minimal perturbation of cellular functions (Lindahl, 1948; Creanor and Mitchison, 1979; Banfalvi, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…[30] One challenge with these methods is that they require a large number of cells for each sample; therefore, an analysis of cell-cycle-dependent translation regulation must involve synchronization. [31] Polysome profiling showed that polysomes remain stable in mitosis when cells are synchronized by double thymidine block, although they are disrupted by nocodazole treatment, [32] again highlighting the impact of the choice of synchronization method. Translation during mitosis was found to be attenuated due to slower elongation, [32,33] which is consistent with the presence of maintained polysomes since polysome profiling cannot distinguish between unaltered active translation and slowed-down elongation.…”
Section: To Translate or What To Translate That Is The Questionmentioning
confidence: 99%